THE INFLUENCE OF SOCIAL MEDIA ON EMERGING LUXURY TRAVEL TRENDS IN UZBEKISTAN - Putri Debbi Herdianty (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract There is a rapid growth in luxury tourism in Uzbekistan, and it is coming along successfully due to the silky road legacy that it had and has been transformed to an exclusive and high-quality tourist destination. The paper aims at discussing how social media, including Instagram, TikTok, and You Tube affect development and promotion of luxury travel in Uzbekistan. Social media is an important part of influencing traveler behavior towards creating visibility of boutique hotels, cultural experience tours, and luxury services. The role of influencer marketing, digital storytelling, and user- generated content is changing to attract tourists to Uzbekistan, because of the incidence of the possibilities of tourists visiting the country. This investigation clarifies the way in which the trend on social media not only influences the expectations of the tourists but also potentially strengthens the locals entrepreneurs, reconfigures brand identities, and rebrands Uzbekistan as a first-rate destination in the Central Asian region.